2022-RA-136-ESGO Columnar epithelium is the original site of most cervical squamous cell cancers. (20th October 2022) - Reich, Olaf; Regauer, Sigrid
Abstract : Introduction/Background: Cervical HPV-research is based on mature squamous epithelium (Woodman, CB. Nat Rev Cancer 2007), however, only a minority of squamous cell cancer (SCC) arise in this type of epithelium. Surprisingly, it was only in the last years that immature squamous metaplastic epithelium in the transformation zone and reserve cells (RC) throughout the columnar epithelium moved into research focus. Methodology: This review will focus on recent aspects of HPV-induced cervical carcinogenesis. Results: UGS-derived p63/CK17-positive RC located within the columnar epithelium are precursor cells for metaplastic squamous epithelium and subsequent HSIL and SCC (Fritsch, Clin Ant 2021; Regauer S. Curr Opin Virol 2021). RC may be target for HPV-infection and act as reservoirs of HPV (Goyal A, Am J Surg Path 2020; Doorbar J, Curr Opin Virol 2021). A HPV-infection of proliferating RC and immature metaplasia that is not controlled by the immune system, allows development of small foci of thin HSIL as result of inhibition of p53- and Rb-protein-mediated cell-cycle processes by E6/7-protein (Reich, Int J Gynecol Pathol 2017; Regauer, Am J Surg Pathol 2021; Regauer, Curr Opin Virol 2021). Enlargement of thin HSIL and stepwise progression from thin to thick HSIL eventually produce larger lesions, and invasion begins from thick HSIL inside the TZ. Conclusion: Contrary to the prevailing opinion, cervical SCC arise most frequently from RC and immature metaplastic epithelium in the TZ. Cervical carcinogenesis is not limited to the SCJ, and cuboidal cells, that accomodates for the difference of epithelial thickness at the SCJ, are of no significance for carcinogenesis.